Analisis dan Rekonstruksi Pengaturan Sanksi Etik Ideal Bagi Advokat Terpidana (Studi Putusan Mahkamah Agung Nomor 176PK/Pid.Sus/2017) - Moniaga, Charles Leonard; Limbong, Henry Maraden; Darari, Andre Falih (Jurnal Hukum Respublica, 2024)
Corruption is a serious problem in Indonesia that needs to be eradicated through law enforcement. However, law enforcers have contributed to corruption, including advocates, such as OC Kaligis, who was found guilty of bribing judges at the Medan State Administrative Court. However, his actions have never been subject to ethical sanctions until now. Therefore, this article examines two issues. First, what is the ideal ethical sanction for advocates convicted of corruption in the perspective of the advocate code of ethics? Second, how should the regulation in the advocate code of ethics be related to ethical sanctions for convicted advocates so that the honour of the advocate profession as officium nobile remains protected? This research is a normative legal research with statute approach, case approach and conceptual approach. The results show that the ideal ethical sanction for advocates convicted of corruption is permanent dismissal from the advocate professional organization. Arrangements related to ethical sanctions for convicted advocates in the advocate code of ethics are still weak so they need to be reconstructed.